Short and medium-term coastal evolution of Necochea Municipality, Buenos Aires province, Argentina - Merlotto, Alejandra (2014)
The short and medium-term coastal evolution of Necochea Municipality, Buenos Aires province (Argentina) was studied. The medium-term evolution study was based on aerial photographs from 1967 and 1984, and satellite images from 2004, using the dune or cliff toe as coastline indicator. The short-term evolution was studied from February 2006 to December 2009 by means of seasonal beach profiles and sediment sampling. Results showed that in the medium-term at Necochea, the coastline has remained stable or has advanced. Whereas in the shortterm, the analysis has evidenced incipient erosion processes. On the other hand, at Queque´n the retreat of the coastline and the negative sedimentary balances (medium and short-term) are clearly indicating an accentuated erosion process. The different degrees of coastal erosion are related in part to beach ulnerability to wave storms but mainly to anthropogenic actions, which have affected the beach sediment supply. These results evidence the necessity to develop a coastal management programme.